Signs and Symbols: Religios and National Dimensions - Ostashchuk, Ivan (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The central issues of this paper are the semantic content and the conceptual interpretation of the notions of symbol and sign in philosophical and religious, linguistic and cultural contexts; the relationship between the logic of symbolic thought and communication. The paper highlights the importance of symbols and signs for transmitting information in religious and national universums